Towards the Implementation of Monetary Management in Islamic Economic System Based on Recent Developments - Hassan, Mohammad Kabir; Shah, Muhammad Abdul Rehman; Alazhari, Manzoor Ahmad; Selim, Mohammad (Universitas Muhammadiyah Yogyakarta, 2021)
Monetary management is an essential part of the objectives of Shari’ah under the umbrella of the preservation of wealth (Ma’al). Our primary sources: Qur’an and Sunn’ah, provide divine legislation on the prohibition of Riba to manage bases of monetary transaction. Further, the juristic tools facilitate scholars to propose solutions to meet the emerging issues on diversified aspects of society. Muslim scholars have always adapted and contributed to the Islamic finance system and regulation, theoretically and practically. In recent decades, Islamic banking and finance has seen strong momentum with double digit growth, fulfilling the monetary requirement of depositors on the liability side along with industry on the asset side. We seek to review the theoretical and empirical literature on Islamic monetary mangement. Monetary management in the Islamic economic context is still an area that needs more research. This paper examines how literature has been developed over time up until modern Islamic economic and banking practices. The findings suggest that Islamic monetary management has been gradually developed in recent years and such development is remarkable steps forward in pursuing Islamic monetary policy independently. In addition, Islamic monetary policy is proved to be relatively more effective compared to interest based conventional monetary policy. The implications of such findings have established new milestones for the central banks of all the countries, including the muslim majority countries for pursuing interest free Islamic monetary policy with full confidence. Furthermore, there are four major views on Islamic monetary policy and the central banks of the world should choose one of the best methods and views for the greater effectiveness of monetary policy because conventional monetary policy has been less effective in bringing full employment and price stability in recent years and financial crisis has crippled the interest based conventional economic systems quite badly.